Graves\' disease treated by complementary medicine leading to thyroid storm: a case report. - Linda Daffini; Ilenia Pirola; Giovanni Saccà; Massimo Salvetti; Carlo Cappelli (Caspian Journal of Internal Medicine, 2021)
Background: Thyroid storm is a rare, life-threatening condition characterized by severe clinical manifestations of thyrotoxicosis and can be precipitated by several factors. We described a thyroid storm precipitated by a long-term treatment using homeopathic medicine containing iodine. Case presentation: A 55-year-old Italian woman was admitted to our Sub-Intensive Care Unit with the diagnosis of congestive heart failure and thyrotoxicosis. She has been diagnosed with Graves’ disease two years before; she refused conventional therapy and in the preceding six months had been using phytotherapeutic and homeopathic medicine. We found serum and urine iodine levels consistent with severe intoxication by iodine (serum iodine: 42100 mcg/L and urinary iodine: 4223 mcg/L, respectively). After a few hours, the patient went into cardiac arrest. She was subjected to invasive ventilation, dialyzed with continuous veno-venous hemofiltration and treated with vasoactive amines. Conclusion: The high level of iodemia manifested in our patient - around a thousand times greater than the normal range and itself associated with fatal outcomes - was caused by long-term homeopathic treatment. This long-term treatment has two consequences: first, iodine load-precipitated hyperthyroidism in thyroid storm, and secondly, it prevents us from treating patients with inorganic iodide.